(untitled) (REMUNOM, 2025)
This study, conducted by the Aqua Brazil Project in partnership with the Federal University of Recôncavo of Bahia (UFRB), presents a detailed analysis of the ornamental aquatic organism production chain in Brazil, focusing on continental, marine, and estuarine fish. The Brazilian market stands out internationally, exporting to the United States, Europe, Asia, South America, and, since 2025, Saudi Arabia. Internationally, ornamental fish are popular Pets, with 22.3 million units sold in 2023 and revenue of R 167.6 million. Approximately 90% of freshwater fish are farmed, while species diversity depends on sustainable harvesting. The study used NCM codes 0301.11.90 and 0301.19.00 on the Comex Stat platform, analyzing volume, value, average price, distribution by state, and international destinations. Between 2013 and 2024, exports decreased from 15.5 million to 2.1 million units (-86.66%) and the total value dropped from US10.4 million to US4.1 million, despite the financial appreciation of species. States such as Amazonas and Pará lead continental exports, while Rio de Janeiro, Ceará, and Espírito Santo predominate in marine species. Regulations IN MAPA n.º 10/2020 and IBAMA Ordinance n.º 102/2022 reorganized the sector, expanding the authorized species, increasing added value, and strengthening competitiveness. Initiatives such as the Aqua Brazil Project are essential for fostering innovation, sustainability, traceability, and expanding the domestic and international markets, consolidating Brazil as a leading player in the ornamental fish trade.